2015
DOI: 10.1111/mec.13326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a bacterial pathogen associated with Porites white patch syndrome in the Western Indian Ocean

Abstract: Porites white patch syndrome (PWPS) is a coral disease recently described in the Western Indian Ocean. This study aimed to isolate and identify potential pathogens associated with PWPS utilizing both culture and nonculture screening techniques and inoculation trials. A total of 14 bacterial strains (those dominant in disease lesions, absent or rare in healthy tissues and considered potential pathogens in a previous study) were cultured and used to experimentally inoculate otherwise healthy individuals in an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The bacteria was also shown to re-emerge and cause vibriosis in shellfish hatcheries on the west coast of North America causing decline in larval oyster production of up to ∼59% in one hatchery (Elston et al, 2008). It has also been demonstrated that strains of this species can also cause disease in massive corals in the Indian Ocean (Sere et al, 2015). Although the functional and ecological significance of the association between this bacteria species and Exaiptasia pallida remains to be discovered, our findings indicate that these widely distributed anemones could be reservoirs of the pathogen Vibrio tubiashii .…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria was also shown to re-emerge and cause vibriosis in shellfish hatcheries on the west coast of North America causing decline in larval oyster production of up to ∼59% in one hatchery (Elston et al, 2008). It has also been demonstrated that strains of this species can also cause disease in massive corals in the Indian Ocean (Sere et al, 2015). Although the functional and ecological significance of the association between this bacteria species and Exaiptasia pallida remains to be discovered, our findings indicate that these widely distributed anemones could be reservoirs of the pathogen Vibrio tubiashii .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in controlled experiments the above stressors have proven insufficient to cause the onset of disease without direct physical injury. Such injury has been shown to occur from contact with macroalgae, direct physical damage and predation for example (Nugues et al, 2004; Nicolet et al, 2013; Séré et al, 2015). For this reason, it has been strongly recommended that any coral reef health monitoring undertaken should consider all possible sign of compromised health and not only those of infectious diseases and bleaching (Raymundo, Couch & Harvell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria was also shown to re-emerge and cause vibriosis in shellfish hatcheries on the west coast of North America causing decline in larval oyster production of up to ~59% in one hatchery (Elston et al 2008). It has also been demonstrated that strains of this species can also cause disease in massive corals in the Indian Ocean (Sere et al 2015). Although the functional and ecological significance of the association between this bacteria species and Exaiptasia pallida remains to be discovered, our findings indicate that these widely distributed anemones could be reservoirs of the pathogen Mauricio Rodriguez-…, 2017-1-2 2:10 PM : :…”
mentioning
confidence: 58%